2022
DOI: 10.1093/ajcn/nqac256
|View full text |Cite
|
Sign up to set email alerts
|

Greater adherence to the 2019 Canada’s Food Guide recommendations on healthy food choices reduces the risk of cardiovascular disease in adults: a prospective analysis of UK Biobank data

Abstract: Background The Canada's Food Guide (CFG) was profoundly revised in 2019, but the extent to which adherence to recommendations on healthy food choices reduces the risk of cardiovascular disease (CVD) is unknown Objectives The aim of this study was to examine how greater adherence to the 2019 CFG's recommendations on healthy food choices influences the risk of incident CVD. Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Dietary indices are often the parameter used to measure diet and CVD incidence in UK Biobank studies ( Figure 2 ). Dietary pattern observations, as opposed to data on a single food group, tend to offer more conclusive findings across the studies, in which a healthy diet is found to be associated with a decrease in CVD incidence and mortality [ 10 , 11 , 12 , 13 , 15 , 16 , 17 , 18 ]. There are several definitions of a healthy diet used in these studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary indices are often the parameter used to measure diet and CVD incidence in UK Biobank studies ( Figure 2 ). Dietary pattern observations, as opposed to data on a single food group, tend to offer more conclusive findings across the studies, in which a healthy diet is found to be associated with a decrease in CVD incidence and mortality [ 10 , 11 , 12 , 13 , 15 , 16 , 17 , 18 ]. There are several definitions of a healthy diet used in these studies.…”
Section: Resultsmentioning
confidence: 99%
“…There are several definitions of a healthy diet used in these studies. These studies emphasise a high consumption of plant-based foods, a moderate intake of animal-based foods, and a limited intake of refined grains, processed meats, sugar-sweetened beverages, and foods high in sodium, saturated fat, and added sugars as the most used characteristics [ 12 , 16 , 17 , 18 ]. Others focused on a plant-based diet [ 11 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the variability of the HEFI-2019 score was sufficient, the HEFI-2019 score was correlated with the Healthy Eating Index (HEI)-2015 (r=0.79) and differences of HEFI-2019 score were found among subgroups with known diet quality differences based on sex, age, and smoking status (18). Finally, a prospective analysis of UK Biobank data suggested that a hypothetical increase in HEFI-2019 score reduces the 11-year risk of cardiovascular disease in middle-aged and older adults (6).…”
Section: The Healthy Eating Food Index (Hefi) 2019mentioning
confidence: 99%
“…The CFG-2007 recommended daily servings based on comprehensive diet simulations, thus ensuring that Dietary Reference Intakes (DRI) were met (2). The latest CFG (2019) adopted a different approach and primarily aims at chronic disease risk reduction (3)(4)(5)(6). In addition, recommendations in CFG-2019 (e.g., "eat more often …") are more flexible than those of CFG-2007 and rely on proportions of food categories to constitute a healthy plate, without recommended quantitative daily servings.…”
Section: Introductionmentioning
confidence: 99%
“…The CFG-2007 recommended daily servings based on comprehensive diet simulations, thus ensuring that Dietary Reference Intake (DRI) were met (2). The latest CFG (2019) adopted a different approach and primarily aims at chronic disease risk reduction (3)(4)(5)(6). In addition, recommendations in CFG-2019 (e.g., "eat more often …") are more flexible than those of CFG-2007 and rely on proportions of food categories to constitute a healthy plate, without recommended quantitative daily servings.…”
Section: Introductionmentioning
confidence: 99%